Preliminary survey, diversity, and population density of mites in banana, Musa AAA (Cavendish subgroup) cv. Williams in Peru - Escobar-Garcia, Hector Alonso (2021)
Banana is produced mainly by smallholder farmers and considered a staple food in many developing countries. This study aimed to evaluate the diversity and population densities of mites in plants of Musa AAA (Cavendish subgroup) cv. Williams in Peru. Mites were collected every fortnight for 14 months (February 2016 to March 2017) from a banana crop system located at the Universidad Nacional de Piura, northwestern Peru. The following species were found: Tetranychus abacae (Tetranychidae), Neoseiulus fallacoides and Euseius concordis (Phytoseiidae). This is the first report for T. abacae and N. fallacoides in Peru. The most abundant mite was T. abacae, which was found in all evaluations and had the lowest populations between June and August, corresponding to the winter time locally. Both N. fallacoides and E. concordis were found in very low numbers. Knowing mite species in banana plants is essential for a proper crop management, mainly for pest control strategies.